Synthesis of poly(γ-tert-butyl L-glutamate): influence of polymerization conditions - Phung , Thi Thuy Dung; Nguyen , Thi Le Thu (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This work presents the synthesis and characterization of poly(γ-tert-butyl L-glutamate)(PtBuLG) via a living ring-opening polymerization procedure of γ-tert-butyl L-glutamate N-carboxyanhydride (tBuLG-NCA). The reaction conditions were investigated to optimize the polymerization yield and molecular weight polydispersity. The synthesized PtBuLG was characterized using nuclear magnetic resonance spectroscopy (NMR), gel permeation chromatography (GPC) and attenuated total reflection-Fourier transform infrared (ATR FT-IR. Finally, hydrolysis of PtBuLG resulted in poly(L-glutamic acid) (PLGA).